Global Killer Ebola: How was it handled by the Indian press? - Paul, Sourabh; Mahajan, Preetam B; Sahoo, Jyotiranjan (Indian Journal of Community Health, 2016)
Background: World has witnessed many devastating outbreaks in the past and ebola outbreak of 2014 is one among them as WHO declared it as “International public health emergency”. Aims & Objectives: To access the coverage of ebola related articles (ERA) in India’s three major English print media. Material & Methodology: A cross sectional study was carried out from June 2014 to March 2015 among three leading national English newspapers of India (Times of India, The Hindu and The Telegraph). “Ebola” was used as a search term to identify the ebola related articles (ERAs) in respective websites of the selected newspapers. All the eligible ERAs were entered into a data extraction form (DEF) for content analysis. Results: Total number of ERAs published during the study period was 967. Hindu (443) was leading followed by Times of India (390) and Telegraph (134). Majority of the ERAs were concern about ebola (30.3%) followed by ebola related activates (28.9%) and ebola as a disease (26.9%). ERAs were mainly published in international section and in the form of news items and source was mentioned properly (50%). Photograph and Infrographics proportion was very minimal. Conclusion: In spite of ERAs presence in English print media there is a need to publish more articles of ongoing epidemics particularly on the front pages, from authentic sources and provide richer information that is suitable for the mass population of the country.